Specific reasons for living and suicide resilience mechanisms negatively predict suicide risk among sexual minorities - Van Zyl, Maryke; Brennan, James Michael; Parmenter, Joshua G.; Joseph, Kaela; Bongar, Bruce; Goldblum, Peter (Frontiers in Social Psychology, 2024)
IntroductionSexual minority (SM) adults experience disproportionately high rates of suicide, yet it is not clear what protective factors offset the risk of suicide.MethodA cross-sectional online survey of 564 SM adults assessed associations between suicide outcomes, suicide resilience and reasons for living (RFL).ResultsSurvival and Coping Beliefs and Moral Objections subscales of the RFL, as well as Suicide Resilience were negatively associated with likelihood of future sucide attempts.ConclusionSuicide resilience and some RFL subscales are protective against suicide for SM adults, which not only supports the use of RFL and resilience among SM adults, but provides an empirical foundation for developing a culturally-specific RFL measure.